ChemInform Abstract: Synthesis of the 3, 4, 5‐Trimethoxy‐2‐(3, 4‐methylenedioxy‐6‐nitrophenyl)benzaldehyde for Divergent Preparation of Cytotoxic Biaryls. Issue 8 (1st March 2013) - Labruere, Raphael; Helissey, Philippe; Desbene‐Finck, Stephanie; Giorgi‐Renault, Sylviane
Abstract An optimized procedure is elaborated for the preparation of the target compound (II) from the known aldehyde precursor (I).